Digital Literacy on Information and Electronic Transactions in the Student Paradigm of SMAN 2 Koto Pariaman - Ukas; Syuryani; Padrisan Jamba; Sari; Lenny Husna; Raju Moh Hazmi; Ragil Surya Prakasa; Zuhdi Arman (PT FORMOSA CENDEKIA GLOBAL, 2023)
Digital literacy is widespread and often addresses key issues. To educate students on digital literacy, it is necessary to develop reading skills, read the content carefully, and then use digital literacy to understand the content. This activity aims to improve the digital literacy skills of teenagers, especially at SMAN 2 Koto Pariaman. The formulation of activity forms, activity stages, and evaluation are the three stages that become the method of implementing PKM activities. The assessment results show that the level of understanding of members about continuing education is very high, and they have awareness about the risks involved in the web and virtual entertainment, as shown by the consequences of the poll of 83.3% related to negative substances on the Web. However, the evaluation results showed that the majority of participants only used the internet to communicate, play games, and use social media, so they did not understand digital literacy regarding the use of the internet for science.